The Impact of Climate Changes on Primary Producer of Aquatic Ecosystem (Phytoplankton) in the Ocean - Hutabarat, Philipus Uli Basa; Sanjayasari, Dyahruri; Syakuri, Hamdan (Fakultas Perikanan dan Ilmu Kelautan, 2024)
Aquatic ecosystems are very important for biodiversity and play a crucial role for the environment as well as for humans. Phytoplankton, the primary producers in this system, significantly contribute to oxygen production and CO2 absorption, making them crucial for global climate regulation. However, climate change marked by rising temperatures and unpredictable weather patterns has negatively impacted the abundance and distribution of phytoplankton, thereby threatening marine biodiversity and the stability of ecosystems. This study focuses on analyzing the impact of climate change on the abundance of phytoplankton in the oceans and identifying strategies to address it, through literature review. The research results indicate a significant decline in phytoplankton abundance, influenced by significant temperature changes from year to year. Effective mitigation strategies, including efforts to reduce greenhouse gases, protect biodiversity, and educate the public, are essential for preserving aquatic ecosystems. This research emphasizes the need for immediate and sustained action to protect marine biodiversity and ensure ecological balance.